Improvement of Bixin Carotenoid Stability through the Formation of M–bixin (M = Mg2+, Ca2+, Zn2+, and Se4+) Complex Compounds Based on Photodegradation Kinetic Studies - Rahmalia, Winda; Shofiyani, Anis; Kusuma Dewi, Yohana Sutiknyawati; Indriani, Fani; Putri, Alintianni Yolla; Septiani, Septiani (Universitas Gadjah Mada, 2024)
Bixin is used in wide-ranging food applications but is susceptible to degradation by many factors, including light. This research aims to increase bixin photostability through metal complexation. Bixin was complexed with Mg2+, Ca2+, Zn2+, and Se4+. The synthesis process was carried out in deep eutectic solvent media. Metal-bixin complexes have been successfully synthesized, indicated by the change in retention factor and %III/II ratio values resulting from thin-layer chromatography and UV-vis spectrophotometer analysis, respectively. The Fourier transform infrared analysis showed the interaction between central metal ion with bixin ligand has occurred by hydroxyl and carbonyl groups of bixin, which was characterized by a decrease in the intensity of the absorption peak in wavenumber 3000–4000 cm−1 (for the –OH carboxylic group vibration) and the peak shift of metal-bixin complexes towards the larger compared to bixin in the range wavenumber 1600–1700 cm−1 (for C=O ester vibrations). First-order photodegradation kinetics studies showed that the metal-bixin complexes were more stable than pure bixin. Se-bixin was four times more stable than pure bixin. Complexation of bixin with metals was shown to be a potential method to increase the stability of bixin, especially against light exposure.